The Identity of "Negeri Seribu Suluk" as the Government's Appreciation of Malay Culture in Riau - Roni Setia Nugraha; Andre Rahmanto; Agung Satyawan (Journal of Social Interactions and Humanities, 2022)
This article discusses how the background of a places’ identity is formed and how it affects it. The identity place describes the place of the reality in it, about how society and infrastructure are constructed. For example, the identity of Negeri Seribu Suluk is the identity of the Rokan Hulu regency, which was formed in 1999. Negeri Seribu Suluk is one of the government's appreciations for Malay culture. This study uses a qualitative method with a descriptive approach. The results show that the identity built is based on Malay culture, close to Islamic nuances. The effects can be seen from two elements, namely the identity of people's places: physical appearance, behaviour, attitudes, and feelings. The other element is the identity of an area: physical forms, symbolic forms, institutional forms, individual perceptions, and collective perceptions.